Students’ Critical Thinking Skills in Writing Analytical Exposition Text - Hardianti, Hardianti; Jabu, Baso; Salija, Kisman (Pascasarjana Universitas Negeri Makassar, 2023)
The objective of this study is to assess the proficiency of students' critical thinking skills in composing analytical exposition texts, as well as to examine their perceptions regarding the development of critical thinking skills in this particular writing genre. The research employed a descriptive qualitative methodology, utilizing data gathering instruments such as observations and interviews. A study was undertaken at SMA Negeri 4 Gowa Regency during the academic year of 2021/2022. The participants in this study consisted of 30 students enrolled in the class XI MIA 3 during the second semester. However, for the purpose of data collection, the researchers selected a subset of 15 students by purposive sampling for interviews. The findings of this study suggest that students frequently commit errors when it comes to utilizing generic structures and language elements in their written analytic exposition texts. Based on the identified faults, the researcher saw that a majority of the students exhibited deficiencies in adhering to the prescribed guidelines of the analytical exposition text. Furthermore, it was noted that critical thinking skills were not adequately incorporated in the writing sessions conducted within this particular class. The observed phenomenon can be attributed to the insufficient comprehension and instruction provided to students within the educational setting, hindering the development of critical skills. Additionally, the absence of thought-provoking inquiries posed by educators may impede students' progress in enhancing their critical thinking abilities. Based on the analysis and observations conducted, the researcher has reached the conclusion that the students of class XI MIA 3 at SMA Negeri 4 Kabupaten Gowa demonstrate a moderate degree of critical thinking skills, as assessed by the critical thinking characteristics outlined by Facione (Facione, 2013).